Anti-Obesity Effects of Soybean Embryo Extract and Enzymatically-Modified Isoquercitrin - Kim, Minsu (Biomolecules, 2020)
Soy isoflavones are bioactive phytoestrogens with known health benefits. Soybean embryo extract (SEE) has been consumed as a source of isoflavones, mainly daidzein, glycitein, and genistein. While previous studies have reported the anti-obesity effects of SEE, this study investigates their molecular mechanisms and the synergistic effects of co-treatment with SEE and enzymatically modified isoquercitrin (EMIQ). SEE upregulated genes involved in lipolysis and brown adipocyte markers and increased mitochondrial content in differentiated C3H10T1/2 adipocytes in vitro. Next, we use a high-fat diet-induced obesity mouse model to determine the anti-obesity effect of SEE. Two weeks of single or combined treatment with SEE and EMIQ significantly reduced body weight gain and improved glucose tolerance. Mechanistically, SEE treatment increased mitochondrial content and upregulated genes involved in lipolysis in adipose tissue through the cAMP/PKA-dependent signaling pathway. These effects required a cytosolic lipase adipose triglyceride lipase (ATGL) expression, confirmed by an adipocyte-specific ATGL knockout mouse study. Collectively, this study demonstrates that SEE exerts anti-obesity effects through the activation of adipose tissue metabolism and exhibits a synergistic effect of co-treatment with EMIQ. These results improve our understanding of the mechanisms underlying the anti-obesity effects of SEE related to adipose tissue metabolism.